PENGARUH KETERIKATAN KARYAWAN (EMPLOYEE ENGAGEMENT) TERHADAP KINERJA KARYAWAN: PERAN JARAK KEKUASAAN (POWER DISTANCE) SEBAGAI MODERATOR (Studi Pada Patra Jasa Convention Hotel Semarang) - Rantelimbong, Octaviani; Mas’ud, Fuad (Diponegoro Journal of Management, 2016)
Employee performance is one of the most important factor in assessing the progress of a company. Performance is influence by several factors, one of them is employee engagement. The purpose of this research is to investigate the effect of employee engagement  and power distance as the moderator variable to employee performance.             This research was done in Patra Jasa Convention Hotel Semarang. The samples number determined in this research are 89 respondents and used purposive sampling method. As independent variable is employee engagement, moderating variable is power distance and dependent variable is employee performance. This research using simple regression and moderated regression analysis to verify and to prove the research hypotesis.            The results of analysis showed that employee engagement has a positive significant influence to employee performance and power distance may moderate relationship between employee engagement to employee performance.